Adaptive capacity: exploring the research frontier. (25th May 2017) - Mortreux, Colette; Barnett, Jon
Abstract : In the past 15 years there has been rapid growth in research on adaptive capacity. This article critically reviews this literature, describing changes in the field over time, and highlighting the new frontiers in research. It explains how research on adaptive capacity began and remains heavily influenced by a one‐size‐fits‐all assets‐based theory that assumes that adaptation action is commensurate with the possession of capitals. It explains how this theory has been unable to explain how adaptation is actually practiced across diverse contexts and scales. The article then highlights new research, particularly that which extends analysis to include psycho‐social and institutional dimensions applied at smaller scales of analysis. This shift recognizes and helps overcome the limits of traditional approaches to adaptive capacity, but the field still lacks theories that can explain the relationship between adaptive capacity and adaptation outcomes. Drawing on findings from disaster risk reduction and behavioral science literatures, this article outlines a framework comprised of six factors that better explain how capacity is translated and mobilized into action, namely: risk attitudes, personal experience, trust in and expectations of authorities, place attachment, competing concerns, and household composition and dynamics. WIREs Clim Change 2017, 8:e467. doi: 10.1002/wcc.467 This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : A word cloud of key terms used in this review of the literature on adaptive capacity.